Periodontal disease, peri-implant disease and levels of salivary biomarkers IL-1β, IL-10, RANK, OPG, MMP-2, TGF-β and TNF-α: follow-up over 5 years - Alex Martins GOMES; Dhelfeson Willya Douglas-; Sérgio Diniz FERREIRA; Tarcília Aparecida da SILVA; Luís Otávio Miranda COTA; Fernando Oliveira COSTA (University of São Paulo, 2019)
Abstract Objective The aim of this study was to evaluate the levels of salivary biomarkers IL-1β, IL-10, RANK, OPG, MMP-2, TG-β and TNF-α in individuals with diagnosis of peri-implant mucositis in the absence or presence of periodontal and peri-implant maintenance therapy (TMPP) over 5 years. Material and Methods Eighty individuals diagnosed with peri-implant mucositis were divided into two groups: one group that underwent periodontal and peri-implant regularly maintenance therapy, called GTP (n=39), and a second group that received no regular maintenance GNTP (n=41). Each participant underwent a complete periodontal and peri-implant clinical examination. Collection of saliva samples and radiographic examination to evaluate peri-implant bone levels were conducted at two times: initial examination (T1) and after 5 years (T2). The salivary samples were evaluated through ELISA for the following markers: IL-1β, IL-10, RANK, OPG, MMP-2, TGF and TNF-α. Results A higher incidence of peri-implantitis was observed in the GNTP group (43.9%) than in the GTP group (18%) (p=0.000). All individuals (n=12) who presented peri-implant mucositis and had resolution at T2 were in the GTP group. After 5 years, there was an increase in the incidence of periodontitis in the GNTP group compared to the GTP group (p=0.001). The results of the study revealed an increase in the salivary concentration of TNF-α in the GNTP group compared to the GTP group. The other salivary biomarkers that were evaluated did not show statistically significant differences between the two groups. Conclusions The salivary concentration of TNF-α was increased in individuals with worse periodontal and peri-implant clinical condition and in those with a higher incidence of peri-implantitis, especially in the GNTP group. Longitudinal studies in larger populations are needed to confirm these findings and elucidate the role of this biomarker in peri-implant disease.